Identification of proliferin mRNA and protein in mouse placenta. - Linzer, D I (1985)
Proliferin is a recently described, prolactin-related protein whose mRNA appears in several murine cell lines during active growth. We have surveyed a number of mouse organs or tissues for the presence of mRNAs that hybridize to cloned proliferin cDNA. Of the tissues tested, only the placenta yielded proliferin-related mRNA. This placental RNA is about 1 kilobase in length, increases sharply between days 8 and 10 of pregnancy, and then gradually declines through day 18. It is more abundant in RNA extracted from the fetal, compared to the maternal, part of the placenta. From a cDNA plasmid library prepared from poly(A)+ placental RNA, two types of proliferin-related clones were isolated, differing in intensity of hybridization to proliferin cDNA. By nucleotide sequence analysis, a strongly hybridizing clone was found to be nearly identical to the proliferin cDNA clone isolated from a library prepared from mRNA of a growing mouse fibroblastic cell line. Using an antiserum prepared against a synthetic proliferin fusion protein, we show that proliferin is secreted as a glycoprotein by minced placental tissue and that it differs from mouse placental lactogen. We conclude that proliferin is a placental hormone that is synthesized in certain mouse cell lines during active growth. Its function during pregnancy and during the growth of cultured cells is presently unknown.